2017
DOI: 10.1073/pnas.1712711114
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of primate prefrontal cortex and medial temporal lobe to temporal-order memory

Abstract: Neuropsychological and neurophysiological studies have emphasized the role of the prefrontal cortex (PFC) in maintaining information about the temporal order of events or items for upcoming actions. However, the medial temporal lobe (MTL) has also been considered critical to bind individual events or items to their temporal context in episodic memory. Here we characterize the contributions of these brain areas by comparing single-unit activity in the dorsal and ventral regions of macaque lateral PFC (d-PFC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 51 publications
7
54
0
Order By: Relevance
“…Interestingly, despite a clear and consistent deficit in spatio-temporal and episodic recall, the spared memory for sequences of objects in WS suggests a relative independence of object-related processes within the episodic system that might rely in part on connections with the prefrontal cortex (Naya et al, 2017). Additionally, this objectrelated success is consistent with spatial navigation studies that show better landmark use in WS compared with children similar in mental age (Lakusta et al, 2010).…”
Section: Atypical Development Of Episodic Memory: Williams Syndromesupporting
confidence: 65%
“…Interestingly, despite a clear and consistent deficit in spatio-temporal and episodic recall, the spared memory for sequences of objects in WS suggests a relative independence of object-related processes within the episodic system that might rely in part on connections with the prefrontal cortex (Naya et al, 2017). Additionally, this objectrelated success is consistent with spatial navigation studies that show better landmark use in WS compared with children similar in mental age (Lakusta et al, 2010).…”
Section: Atypical Development Of Episodic Memory: Williams Syndromesupporting
confidence: 65%
“…The current results are consistent with previous findings in the monkey. A recent investigation of single-neuron activity across shorter timescales (within a ∼1 s delay) identified timevarying responses in the hippocampus, but not the entorhinal cortex 13 . However, in earlier work with longer trial durations, entorhinal neurons exhibited response dynamics across several seconds 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Building on pioneering work demonstrating a spatial code in the hippocampus and entorhinal cortex 6,7 , recent research has shown that hippocampal representations also carry information about the time at which past events took place, suggesting that the MTL maintains a representation of spatiotemporal context in support of episodic memory [8][9][10] . Although a great deal is known about the temporal coding properties of neurons in the hippocampus, the temporal code in the entorhinal cortex, which provides the majority of the cortical input to the hippocampus is less understood, but see [11][12][13][14] .Hippocampal time cells provide a record of recent events including explicit information about when an event occurred. Analogous to hippocampal place cells that fire when an animal is in a circumscribed region of physical space 6, 15 , hippocampal time cells fire during a circumscribed period of time within unfilled delays 8,9,16 .…”
mentioning
confidence: 99%
“…We also constructed individual brain atlases based on the electrophysiological properties around the tip of the electrode (e.g., grey matter, white matter, sulcus, lateral ventricle, and bottom of the brain). The recording sites were estimated by combining the individual MRI atlases and physiological atlases (45).…”
Section: Electrophysiological Recordingmentioning
confidence: 99%